Financial Accounting Theory - William R. Scott (Pearson, 2015)
This newly revised text provides a theoretical approach to financial accounting in Canada, without overlooking institutional structure and standard setting. Important research papers are selected for description and commentary, while extensive references to other research papers underlie the text discussion.